Preclinical evaluation of the efficacy of an antibody to human SIRPα for cancer immunotherapy in humanized mouse models - Saito, Yasuyuki; Iida-Norita, Rie; Afroj, Tania; Refaat, Alaa; Hazama, Daisuke; Komori, Satomi; Ohata, Shinya; Takai, Tomoko; Oduori, Okechi S.; Kotani, Takenori; Funakoshi, Yohei; Koma, Yu-Ichiro; et al. (Frontiers in Immunology, 2023)
Tumor-associated macrophages (TAMs) are abundant in the tumor microenvironment and are considered potential targets for cancer immunotherapy. To examine the antitumor effects of agents targeting human TAMs in vivo, we here established preclinical tumor xenograft models based on immunodeficient mice that express multiple human cytokines and have been reconstituted with a human immune system by transplantation of human CD34 + hematopoietic stem and progenitor cells (HIS-MITRG mice). HIS-MITRG mice supported the growth of both human cell line (Raji)-and patient-derived B cell lymphoma as well as the infiltration of human macrophages into their tumors. We examined the potential antitumor action of an antibody to human SIRPα (SE12C3) that inhibits the interaction of CD47 on tumor cells with SIRP on human macrophages and thereby promotes Fcγ receptor-mediated phagocytosis of the former cells by the latter. Treatment with the combination of rituximab (antibody to human CD20) and SE12C3 inhibited Raji tumor growth in HIS-MITRG mice to a markedly greater extent than did rituximab monotherapy. This enhanced antitumor effect was dependent on human macrophages and attributable to enhanced rituximab-dependent phagocytosis of lymphoma cells by human macrophages. Treatment with rituximab and SE12C3 also induced reprogramming of human TAMs toward a proinflammatory phenotype. Furthermore, the combination treatment essentially prevented the growth of patient-derived diffuse large B cell lymphoma in HIS-MITRG mice. Our findings thus support the study of HIS-MITRG mice as a model for the preclinical evaluation in vivo of potential therapeutics, such as antibodies to human SIRPα, that target human TAMs.